2019
DOI: 10.18502/sjms.v14i3.5211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hepatitis B Infection among Pregnant Women attending Antenatal Clinic in UM Dafog Area, South Darfur State, Sudan

Abstract: Background: Sudan is an endemic country for hepatitis B virus (HBV). Screening for HBV during pregnancy may help in instituting interventions to minimize vertical transmission. HBV in pregnant women in remote areas of Darfur were uncovered by the previous studies in Sudan, Objectives: This study was aimed to determine the seroprevalence of HBV and the possible risk factors for its acquisition among antenatal care attendants in Um Dafog area, South Darfur State, Sudan. Materials and Methods: A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
2
1
3
Order By: Relevance
“…12 However, the seroprevalence data are similar (3.3%) to the results found in national, representative dried blood spot samples that were collected during the 2013-2014 Demographic and Health Survey, which sought to determine the HBV prevalence among adults and children living in the DRC. 13 Compared with other countries, the seroprevalence rate we found is also lower than that found in Uganda (where 11.8% pregnant women tested positive for HBsAg), 14 in Congo-Brazzaville (8.7%), 15 in South Sudan (11%), 16 in Sudan (8.5%), 17 and in Cameroon (9.4%). 18 However, this seroprevalence rate turns out to be superior to that found in Pointe-Noire, Congo-Brazzaville (2.6%).…”
Section: Discussioncontrasting
confidence: 68%
“…12 However, the seroprevalence data are similar (3.3%) to the results found in national, representative dried blood spot samples that were collected during the 2013-2014 Demographic and Health Survey, which sought to determine the HBV prevalence among adults and children living in the DRC. 13 Compared with other countries, the seroprevalence rate we found is also lower than that found in Uganda (where 11.8% pregnant women tested positive for HBsAg), 14 in Congo-Brazzaville (8.7%), 15 in South Sudan (11%), 16 in Sudan (8.5%), 17 and in Cameroon (9.4%). 18 However, this seroprevalence rate turns out to be superior to that found in Pointe-Noire, Congo-Brazzaville (2.6%).…”
Section: Discussioncontrasting
confidence: 68%
“…Other known factors are associated with HBV infection such as unprotected sex, However, history of surgery, long hospital stay, excision, scari cation, acupuncture were not associated with HBV Our results are consistent those of Mudardum and Mohammed in Sudan [20] and Bayo et al in Ouangda [32]. However, Umare et al ( 2016…”
Section: Discussionsupporting
confidence: 86%
“…Our results are comparable with recent studies conducted in pregnant women in Ethiopia (7.3% (95% CI: 5-9)) [16] and in Cameroon (7.7%) [17]. By contrast, the seroprevalence of HBV in our study was lower than those reported in northern Cameroon (20%) [18], in Sudan (8.5%) and in South Sudan (11%) [19,20 ], These regions are plagued by politico-military instability, making the health system fragile. The we found in pregnant women in N'djamena is than that reported in studies conducted in other African countries such as Eritrea [21], another study and Egypt in 2020 [23] ( 3.2%; 4.98% and 5% respectively).…”
Section: Discussionsupporting
confidence: 85%
“…However, the result of this study was lower than the result reported from Gedeo zone at 9.2%, 19 Jigjiga town at 8.5%, 38 Gambella at 7.9%, 39 Yirgalem hospital at 7.2%, 40 Ghana at 7.7%, 41 South Darfur state, Sudan at 8.5% 42 , and Gambia at 9.2%. 43 The variation might be due to the differences in geographical regions, sociodemographic variations, differences in cultural practices, and risky behavior toward the risk of HBV infection.…”
Section: Discussioncontrasting
confidence: 84%